Factors Affecting The Use Of Digital Financial Services Among Moslems: An Attempt To Extend The Technology Acceptance Model - Poppy Dian Indira Kusuma; Bambang Agus Pramuka; Sugiarto; Icuk Rangga Bawono (Jurnal Reviu Akuntansi dan Keuangan, 2022)
Digital financial services has been popular, particularly in the Covid-19 pandemic where human mobility is limited and sosial distancing is strictly enforced. Therefore, it is not surprising if the use of digital financial services has been increasingly significant. Based on Technology Acceptance Model (TAM), this study aims at examining the effect of perceived benefit and perceived ease of use on moslems’ intention to adopt digital financial services. To improve the explanatory power of TAM, this study also examines the effect of halal integrity and digital leadership which are expected to be relevant for moslems and implementing at individual level. Quantitative data were obtained from 92 respondents which were selected using convenience technique sampling. Data were analyzed using multiple linear regression and the findings indicate that perceived benefit, perceived ease of use, and digital leadership have a positive effect on moslems intention to use digital financial services. These findings imply that digital technology providers need to pay attention to these three key factors when developing a new digital technology, particularly in case of moslems adopters.